Respuesta :

To answer this question, we can use the explicit formula of an arithmetic sequence:

[tex]a_n=a_1+(n-1)d[/tex]

• We have that the first term (a1) of the arithmetic sequence is 6 (a1 = 6).

,

• The common difference is 3 (d = 3).

Then, we have that the formula is:

[tex]a_n=6+(n-1)\cdot3=6+3(n-1)[/tex]

We can use this formula to find the 20th term of this arithmetic sequence as follows:

[tex]a_{20}=6+3\cdot(20-1)=6+3\cdot(19)=6+57=63\Rightarrow a_{20}=63[/tex]

In summary, the formula for the arithmetic sequence is:

[tex]a_n=6+3(n-1)[/tex]

And the 20th term is equal to 63.

Ver imagen AadaE413454